2005
DOI: 10.1007/s11060-004-9177-z
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary spinal cord metastases in breast cancer: report of four cases and review of the literature

Abstract: Intramedullary spinal cord metastases (ISCM) are usually the result of rapidly progressing systemic cancer. Breast cancer represents one of the most common solid tumors associated with the development of ISCM at rather advanced stages of disease. In the present report we describe four new cases with advanced breast cancer developing ISCM. All cases presented herein indicated that ISCM is a late manifestation of disseminated breast cancer. Three of these patients had been treated for approximately 1-3 years for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
1
28
0
2
Order By: Relevance
“…The routine imaging modality generally used for the diagnosis of intramedullary spinal cord metastasis is MRI. Other imaging techniques (CT, PET/CT, and angiography) are of limited significance (15,16). PET has a sensitivity rate of 96% in detecting spinal metastasis.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…The routine imaging modality generally used for the diagnosis of intramedullary spinal cord metastasis is MRI. Other imaging techniques (CT, PET/CT, and angiography) are of limited significance (15,16). PET has a sensitivity rate of 96% in detecting spinal metastasis.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…The metastasis of IDC to the CNS is generally a late feature of metastatic disease, and is thought to be hematogenous in origin 17) . Among them, about 90% cause brain metastases, and only 8% spread to the leptomeninges 12) . Once the tumor cells reach the leptomeninges, they are thought to spread to the spinal cord via the CSF 17) .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of intramedullary tumors in various studies of metastases affecting the spinal cord ranges from 0.1% to 6% incidence of central nervous system metastases, usually multifocal 4,13,14) . Metastatic tumors are mostly localized in the brain followed by the cerebellum, dura mater, brain stem, and intramedullary spinal cord 12) . In a later review of ISCM by Edelson et al 6) the incidence if ISCM was found to be 3.4%.…”
Section: Discussionmentioning
confidence: 99%
“…O quadro clínico é dependente do nível da lesão na medula espinhal, podendo ocorrer dor localizada ou de distribuição radicular, déficit motor e sensitivo, disfunção vesical e esfincteriana e síndrome de Bro w n -S é q u a rd , sendo a fraqueza muscular o sintoma mais freq ü e n t e 4 , 1 6 , 1 7 . Em 75% dos pacientes investigados o int e rvalo entre o aparecimento dos sintomas neuro l ó-gicos e o desenvolvimento do déficit neuro l ó g i c o completo é inferior a 1 mês 18,19 .…”
Section: Discussionunclassified